Everyday Outdoor Music Life in Galician Cracow - Woźna-Stankiewicz Małgorzata (Musicology Today)
The paper characterises music-involving cultural practices in Cracow’s urban parks, squares, streets, and ice rinks in the period of the so-called Galician Autonomy (1866–1918). Typologies of the spaces where music was performed and of open-air events involving music have been proposed. Music repertoires and performers have been discussed. The main sources for this text are press materials, memoirs, regulations, sheet music, and iconography.